Jenis-Jenis Cendawan dari Ampas Ecoenzyme dengan Sumber Bahan Organik Berbagai Jenis Kulit Jeruk - Sukma Yuliana; Dezi Handayani (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
Ecoenzyme is a solution resulting from the simple fermentation of organic waste with the addition of sugar and water using selective microorganisms such as yeast and bacteria. In general, ecoenzymes are made from vegetable and fruit waste that has not been processed. One of the best organic ingredients to use is orange peel because it is the easiest to get and produces a distinctive and sharp aroma. The purpose of this study was to determine the types of fungi from ecoenzyme dregs with organic material sources of various types of orange peel. This research is a descriptive study which was conducted in June-December 2021 at the Research Laboratory of the Biology Department, FMIPA UNP. The ecoenzyme samples used were a combination of several types of citrus such as Pasaman orange peel, Gunung Omeh orange, lime, and kaffir lime. The results showed that 1 fungal isolate was obtained from the ecoenzyme sample. The results of macroscopic and microscopic observations generally have the same characteristics as colonies, which are brownish white in color, have a rough texture, wavy edges, slow growth, flat rod-shaped cells and quite long, each having 1 cell nucleus. With these characteristics, it shows that the isolates obtained are yeasts. Therefore, it can be concluded that we have succeeded in isolating one fungal isolate from ecoenzyme dregs with organic material sources of various types of orange peel.